A method for preparing tea residue activated carbon for efficient adsorption of ciprofloxacin

By combining the physical and chemical activation method of tea residue, the problem of new materials processing in the existing technology is solved, the effect of efficient adsorption of ciprofloxacin is achieved, and the production cost is reduced, and it has good environmental protection and economic value is achieved.

CN119774608APending Publication Date: 2025-04-08FUJIAN XINSEN CARBON
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411990397.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art, when adsorption of ciprofloxacin in water by using adsorption method, new materials are required to be processed, resulting in consumption of new materials and high costs.

Method used

Through the combination of physical and chemical activation methods, tea residues are used to prepare activated carbon that is highly effective in adsorbing ciprofloxacin, including hydrothermal carbonization, centrifugal drying, activation and rinsing and drying.

Benefits of technology

It has achieved efficient adsorption of ciprofloxacin, and the adsorption rate can reach 98.68%, which is better than the adsorbent prepared by traditional methods. At the same time, it reduces production costs and has good environmental protection and economic value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a method for preparing tea residue activated carbon for efficient adsorption of ciprofloxacin. The method comprises the following steps: a mixed carbonization step, a centrifugal drying step, an activation step and a rinsing and drying step. The specific surface area of ​​the tea residue activated carbon obtained by the preparation method is between 1700-2100m 2 / g, the iodine value is within 1500-1800mg / g, and the tea residue activated carbon obtained by the preparation method can be used in water containing ciprofloxacin antibiotics to adsorb, degrade and remove ciprofloxacin. The tea activated carbon prepared by this scheme uses tea residue as a raw material, and is prepared into an adsorbent by physical and chemical methods. It has low cost, realizes resource recycling, has high environmental protection and economic value, and has a good adsorption effect on ciprofloxacin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmental governance, and in particular to a method for preparing tea residue activated carbon capable of efficiently adsorbing ciprofloxacin. Background Art

[0002] With the rapid development of the pharmaceutical industry, antibiotics such as ciprofloxacin are widely used. However, due to the stable structure of ciprofloxacin, it is difficult to degrade and be absorbed by the human body. Therefore, a large amount of ciprofloxacin that has not been metabolized and degraded enters the environment, causing serious pollution to the ecological environment such as water bodies and soil, threatening human health. Traditional treatment technologies include adsorption, biodegradation, photocatalysis and chemical oxidation. Among them, the adsorption method has become an ideal treatment method for antibiotic wastewater treatment due to its high treatment efficiency, simple operation and low cost. Commonly used adsorbents in the adsorption method include montmorillonite, biomass activated carbon, graphene oxide, etc. Among them, biomass activated carbon is an excellent adsorption material made by pyrolysis of biomass under anaerobic conditions. It has superior properties such as high specific surface area, large pore volume and high dielectric constant, and can effectively achieve physical and chemical adsorption.

[0003] As an effective adsorbent raw material in environmental governance, it is better to use tea residues as adsorbents rather than using other raw materials as adsorbents, which need to be processed from the source. In particular, tea residues are "waste materials" formed after tea has achieved its main drinking function. If tea residues can be used as adsorbents, the effect of turning waste into treasure can be achieved. By using tea residues as biomass to prepare activated carbon, it not only has a higher number of surface functional groups, but also the tea residues themselves have a porous structure, which is conducive to the formation of micropores in activated carbon and improves adsorption capacity. If biochar is prepared from tea residues, the discarded tea residues can not only reduce domestic waste, but also be used as one of the low-cost raw materials for producing efficient biochar, with good practical application potential. Summary of the invention

[0004] (1) Technical issues to be solved

[0005] The purpose of the present invention is to provide a method for preparing tea residue activated carbon that can efficiently adsorb ciprofloxacin, which overcomes the problem that in the prior art, when using the adsorption method to adsorb ciprofloxacin in water, the raw materials used are often new materials, and the new materials need to be processed so that the final product becomes an adsorbent material for water adsorption, which is a preparation method that consumes new materials. The present invention adopts an energy-saving preparation method that turns waste into treasure, and prepares tea residue activated carbon by combining physical and chemical activation methods;

[0006] Sodium chloride can react with carbon materials under high temperature environment, and the surface and internal structure of carbon are etched to remove some carbon atoms in carbon materials. In this process, oxidative activated gas is continuously introduced to corrode the surface of carbonized materials to further expand the originally blocked pores in carbonized materials. At the same time, tar and uncarbonized materials are also removed, thereby increasing the specific surface area of ​​materials and generating a developed pore structure. This is conducive to improving adsorption performance, thereby having a higher adsorption selectivity for ciprofloxacin antibiotics in the environment, conforming to the development of the market, and also having profound significance for waste utilization and environmental protection.

[0007] (2) Technical solution

[0008] In order to solve the above technical problems, the first aspect of the present invention provides:

[0009] A method for preparing tea residue activated carbon for efficient adsorption of ciprofloxacin comprises the following steps:

[0010] S1, mixed carbonization process: weigh tea residue powder and 10%-25% sodium chloride in a mass ratio of 1: (1-5), and then place it in a hydrothermal kettle for hydrothermal carbonization. The hydrothermal carbonization temperature is controlled at 150°C-250°C, and the hydrothermal carbonization time is controlled at 3-5h;

[0011] S2, centrifugal drying process: take out the hydrothermal carbonization product and place it in a centrifuge for 2-3 minutes, and the centrifugal speed is controlled at 500-1000rpm, then take out the solid matter and place it in an electric oven, and dry it in an oven at 90-105℃ for 10-15h;

[0012] S3, activation process: after the solid material of S2 is dried, it is placed in an atmosphere rotary kiln, the temperature is set and carbon dioxide is introduced as an activation gas for activation, and the activation time is controlled to be 1-4 hours;

[0013] S4, rinsing and drying process: the product activated in S3 is cooled to room temperature and then taken out, rinsed to neutrality, and then dried in an oven for 10-12 hours, and stored for later use to obtain the product tea residue activated carbon.

[0014] Preferably, in the step S3, the activation temperature in the atmosphere rotary kiln is controlled at 800-900°C, and the heating rate is controlled at 10-15°C / min.

[0015] Preferably, in step S3, the activation temperature in the atmosphere rotary kiln is controlled to be 900°C, and the heating rate is 10°C / min.

[0016] Preferably, in the S3 step, the activation time is 1-1.5h.

[0017] Preferably, in step S1, the mass fraction of the selected sodium chloride is in the range of 10-25%.

[0018] Preferably, the mass fraction of sodium chloride in step S1 is 20%. In step S1, tea residue powder is mixed with 20% sodium chloride in a mass ratio of 1:3, and then placed in a hydrothermal kettle for hydrothermal carbonization. The hydrothermal carbonization temperature is controlled at 200°C-230°C, and the hydrothermal carbonization time is controlled at 3-4h.

[0019] The second aspect of the present invention provides:

[0020] A tea residue activated carbon, wherein the tea residue activated carbon is prepared by any one of the above preparation methods.

[0021] Preferably, the specific surface area of ​​the tea residue activated carbon obtained is 1700-2100m 2 / g, and the iodine value is within 1500-1800mg / g.

[0022] Preferably, the specific surface area of ​​the tea residue activated carbon obtained is 1900-2100m 2 / g, and the iodine value is within 1700-1800mg / g.

[0023] The third aspect of the present invention provides:

[0024] An application of the tea residue activated carbon is to use the tea residue activated carbon prepared by the above method as an adsorbent to adsorb, degrade and remove ciprofloxacin in a water body containing the ciprofloxacin antibiotic.

[0025] (3) Beneficial effects

[0026] The present invention uses tea residue as a raw material, and prepares an adsorbent by physical and chemical methods. The cost is low, resource recycling is achieved, and the adsorbent has a high environmental economic value. At the same time, the environment is protected, and the adsorbent has a green environmental effect. The present invention uses a physical-chemical preparation method in which tea residue is impregnated with sodium chloride and then activated with high-temperature carbon dioxide to prepare an adsorbent with a specific surface area of ​​2084 m 2 / g, and a pore volume of 1.63cm3 / g, which is a high-performance tea residue activated carbon, has greatly improved specific surface area and pore volume than the tea residue activated carbon prepared by chemical method only; at the same time, the adsorption rate of tea residue activated carbon prepared by chemical method is only 62.45%, while the adsorption rate of tea residue activated carbon prepared by the physical-chemical method of this scheme can reach 98.68%, and the adsorption effect is good; in general, the production process of the present invention is not demanding, the process flow is simple, the production cycle is short, the production is more convenient and quick, it has more obvious advantages, has a good market prospect, and is suitable for large-scale promotion and use. DETAILED DESCRIPTION

[0027] The present invention is described in detail below using different manufacturing processes. The enumerated embodiments can enable technicians in this field to better understand the present invention, but do not limit the present invention in any form. For example, the present invention can be expanded to the production of aluminum alloys of other strengths or other alloys with the same characteristics for application.

[0028] Embodiment 1:

[0029] The tea residues were fully mixed with 20% sodium chloride solution in a mass ratio of 1:3 and then soaked for 24 hours. Then, they were placed in a 230℃ hydrothermal kettle for hydrothermal carbonization for 4 hours, and then taken out and dried at 105℃ for 10 hours. After drying, they were placed in an atmosphere rotary furnace for activation. The temperature of the activation furnace was set at 900℃, the heating rate was 10℃ / min, and carbon dioxide was introduced as the activation gas for activation. The activation time was 1.5 hours. After cooling, they were taken out, first boiled and washed directly with 10% hydrochloric acid three times, then boiled and washed with pure water five times, and then directly adjusted to PH 6-7 with ammonium bicarbonate. Finally, they were washed with pure water 5 times, and then placed in an oven for drying to obtain tea residue activated carbon. The obtained activated carbon was subjected to an oscillation adsorption test with the prepared ciprofloxacin solution, and the adsorption rate was measured to be 98.68%.

[0030] Among them, the detection method in the adsorption test is: accurately weigh 0.05g of ciprofloxacin powder in a beaker, then add 5mL of 0.1mol / L hydrochloric acid to dissolve ciprofloxacin. Transfer the dissolved ciprofloxacin to a 100mL volumetric flask, wash the beaker with distilled water several times, and finally adjust the volumetric flask to the scale line to prepare 0.5000mg / mL of ciprofloxacin reserve. According to the proportion, 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, and 0.80mL of 0.5000mg / mL ciprofloxacin stock solution are respectively placed in a 50mL volumetric flask, and then an appropriate amount of distilled water is added to the bottle mouth, shaken and mixed, and a series of ciprofloxacin standard solutions of different concentrations are prepared, with concentrations of 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, and 0.008mg / mL, respectively. The absorbance was measured by ultraviolet spectrophotometer at a wavelength of 277nm, and hydrochloric acid solution was used as a control. By setting the hydrochloric acid solution as a control group, it was shown that the hydrochloric acid solution itself had no effect on the adsorption rate, so the experimental data obtained were accurate. Each group of measurements was performed 3 times, and the average value was calculated. Subsequently, a standard curve was drawn based on the relationship between the absorbance and the concentration of the ciprofloxacin solution, and the regression line equation was obtained as follows: y = 0.00615-134.87568*x, R2 = 0.9998. Take the dried tea residue activated carbon in Example 1, and then pipette 25mL of 0.05mg / mL ciprofloxacin solution and add it, and perform 1-3h oscillation adsorption on a constant temperature shaking bed at a speed of 100-200rmp / min and a temperature of 20-30°C. After the adsorption experiment was completed, the supernatant was removed using a 5mL syringe and filtered through a 0.45 micron aqueous disposable syringe filter. 0.01mol / L hydrochloric acid was used as a reference solution, and the absorbance was detected by a UV-visible spectrophotometer. The absorption wavelength of ciprofloxacin was 277nm, and the solution concentration was calculated according to the standard curve. Each group of absorbance was measured three times, and the average was taken. The solution concentration was brought into the adsorption rate and adsorption amount formula to calculate the adsorption rate and adsorption amount, and finally the adsorption rate of the tea residue activated carbon in Example 1 was 98.68%.

[0031] Comparative Example: Purchase the existing activated carbon materials on the market, select the same weight as the finished tea residue activated carbon in Example 1 for adsorption test, and after multiple tests and detections, the average adsorption rate is 62.45%.

[0032] Embodiment 2:

[0033] The tea residues were fully mixed with 15% sodium chloride solution in a mass ratio of 1:1 and then soaked for 24 hours. Then, they were placed in a 150℃ hydrothermal kettle for hydrothermal carbonization for 3 hours, and then taken out and dried at 90℃ for 15 hours. After drying, they were placed in an atmosphere rotary furnace for activation (the activation furnace temperature was set at 800℃, and the heating rate was 15℃ / min), and carbon dioxide was introduced as the activation gas for activation, and the activation time was 1 hour. After cooling, they were taken out, first boiled and washed directly with 10% hydrochloric acid three times, then boiled and washed with pure water five times, and then directly adjusted to PH 6-7 with ammonium bicarbonate, and finally washed with pure water 5 times, and then placed in an oven for drying to obtain tea residue activated carbon. The obtained activated carbon was subjected to an oscillation adsorption test with the prepared ciprofloxacin solution, and the adsorption rate was measured to be 97.89%.

[0034] Among them, the detection method in the adsorption test is: accurately weigh 0.05g of ciprofloxacin powder in a beaker, then add 5mL of 0.1mol / L hydrochloric acid to dissolve ciprofloxacin. Transfer the dissolved ciprofloxacin to a 100mL volumetric flask, wash the beaker with distilled water several times, and finally adjust the volumetric flask to the scale line to prepare 0.5000mg / mL of ciprofloxacin reserve. According to the proportion, 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, and 0.80mL of 0.5000mg / mL ciprofloxacin stock solution are respectively placed in a 50mL volumetric flask, and then an appropriate amount of distilled water is added to the bottle mouth, shaken and mixed, and a series of ciprofloxacin standard solutions of different concentrations are prepared, with concentrations of 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, and 0.008mg / mL, respectively. The absorbance was measured by ultraviolet spectrophotometer at a wavelength of 277nm, and hydrochloric acid solution was used as a control. By setting the hydrochloric acid solution as a control group, it was shown that the hydrochloric acid solution itself had no effect on the adsorption rate, so the experimental data obtained were accurate. Each group of measurements was performed 3 times, and the average value was calculated. Subsequently, a standard curve was drawn based on the relationship between the absorbance and the concentration of the ciprofloxacin solution, and the regression line equation was obtained as follows: y = 0.00615-134.87568*x, R2 = 0.9998. The dried tea residue activated carbon in Example 2 was taken, and 25mL of 0.05mg / mL of ciprofloxacin solution was pipetted and added, and 1-3h of oscillation adsorption was performed on a constant temperature shaking bed at a speed of 100-200rmp / min and a temperature of 20-30°C. After the adsorption experiment was completed, the supernatant was removed using a 5mL syringe and filtered through a 0.45 micron aqueous disposable syringe filter. 0.01mol / L hydrochloric acid was used as a reference solution, and the absorbance was detected by a UV-visible spectrophotometer. The absorption wavelength of ciprofloxacin was 277nm, and the solution concentration was calculated according to the standard curve. Each group of absorbance was measured three times, and the average was taken. The solution concentration was brought into the adsorption rate and adsorption amount formula to calculate the adsorption rate and adsorption amount, and finally the adsorption rate of the tea residue activated carbon in Example 2 was 97.89%.

[0035] Embodiment 3:

[0036] The tea residue was fully mixed with 25% sodium chloride solution in a mass ratio of 1:5 and then immersed for 24 hours. It was then placed in a 250°C hydrothermal kettle for hydrothermal carbonization for 5 hours, and then taken out and dried at 100°C for 13 hours. After drying, it was placed in an atmosphere rotary furnace for activation (the activation furnace temperature was set at 850°C, and the heating rate was 12°C / min), and carbon dioxide was introduced as the activation gas for activation, and the activation time was 3 hours. After cooling, it was taken out, first boiled and washed directly with 10% hydrochloric acid three times, then boiled and washed with pure water five times, and then directly adjusted to PH 6-7 with ammonium bicarbonate, and finally washed with pure water 5 times, and then placed in an oven for drying to obtain tea residue activated carbon. The obtained activated carbon was subjected to an oscillation adsorption test with the prepared ciprofloxacin solution, and the adsorption rate was measured to be 98.23%.

[0037] Among them, the detection method in the adsorption test is: accurately weigh 0.05g of ciprofloxacin powder in a beaker, then add 5mL of 0.1mol / L hydrochloric acid to dissolve ciprofloxacin. Transfer the dissolved ciprofloxacin to a 100mL volumetric flask, wash the beaker with distilled water several times, and finally adjust the volumetric flask to the scale line to prepare 0.5000mg / mL of ciprofloxacin reserve. According to the proportion, 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, and 0.80mL of 0.5000mg / mL ciprofloxacin stock solution are respectively placed in a 50mL volumetric flask, and then an appropriate amount of distilled water is added to the bottle mouth, shaken and mixed, and a series of ciprofloxacin standard solutions of different concentrations are prepared, with concentrations of 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, and 0.008mg / mL, respectively. The absorbance was measured by ultraviolet spectrophotometer at a wavelength of 277nm, and hydrochloric acid solution was used as a control. By setting the hydrochloric acid solution as a control group, it was shown that the hydrochloric acid solution itself had no effect on the adsorption rate, so the experimental data obtained were accurate. Each group of measurements was performed 3 times, and the average value was calculated. Subsequently, a standard curve was drawn based on the relationship between the absorbance and the concentration of the ciprofloxacin solution, and the regression line equation was obtained as follows: y = 0.00615-134.87568*x, R2 = 0.9998. Take the dried tea residue activated carbon in Example 3, and then pipette 25mL of 0.05mg / mL ciprofloxacin solution and add it, and perform 1-3h oscillation adsorption on a constant temperature shaking bed at a speed of 100-200rmp / min and a temperature of 20-30°C. After the adsorption experiment was completed, the supernatant was removed using a 5mL syringe and filtered through a 0.45 micron aqueous disposable syringe filter. 0.01mol / L hydrochloric acid was used as a reference solution, and the absorbance was detected by a UV-visible spectrophotometer. The absorption wavelength of ciprofloxacin was 277nm, and the solution concentration was calculated according to the standard curve. Each group of absorbance was measured three times, and the average was taken. The solution concentration was brought into the adsorption rate and adsorption amount formula to calculate the adsorption rate and adsorption amount, and finally the adsorption rate of the tea residue activated carbon in Example 3 was 98.23%.

[0038] Embodiment 4:

[0039] The tea residues were fully mixed with 10% sodium chloride solution in a mass ratio of 1:4 and then soaked for 24 hours. Then, they were placed in a 200℃ hydrothermal kettle for hydrothermal carbonization for 4 hours, and then taken out and dried at 105℃ for 14 hours. After drying, they were placed in an atmosphere rotary furnace for activation. The temperature of the activation furnace was set at 900℃, the heating rate was 15℃ / min, and carbon dioxide was introduced as the activation gas for activation. The activation time was 4 hours. After cooling, they were taken out, first boiled and washed directly with 10% hydrochloric acid three times, then boiled and washed with pure water five times, and then directly adjusted to PH 6-7 with ammonium bicarbonate. Finally, they were washed with pure water 5 times and then placed in an oven for drying to obtain tea residue activated carbon. The obtained activated carbon was subjected to an oscillation adsorption test with the prepared ciprofloxacin solution, and the adsorption rate was measured to be 98.44%.

[0040] Among them, the detection method in the adsorption test is: accurately weigh 0.05g of ciprofloxacin powder in a beaker, then add 5mL of 0.1mol / L hydrochloric acid to dissolve ciprofloxacin. Transfer the dissolved ciprofloxacin to a 100mL volumetric flask, wash the beaker with distilled water several times, and finally adjust the volumetric flask to the scale line to prepare 0.5000mg / mL of ciprofloxacin reserve. According to the proportion, 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, and 0.80mL of 0.5000mg / mL ciprofloxacin stock solution are respectively placed in a 50mL volumetric flask, and then an appropriate amount of distilled water is added to the bottle mouth, shaken and mixed, and a series of ciprofloxacin standard solutions of different concentrations are prepared, with concentrations of 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, and 0.008mg / mL, respectively. The absorbance was measured by ultraviolet spectrophotometer at a wavelength of 277nm, and hydrochloric acid solution was used as a control. By setting the hydrochloric acid solution as a control group, it was shown that the hydrochloric acid solution itself had no effect on the adsorption rate, so the experimental data obtained were accurate. Each group of measurements was performed 3 times, and the average value was calculated. Subsequently, a standard curve was drawn based on the relationship between the absorbance and the concentration of the ciprofloxacin solution, and the regression line equation was obtained as follows: y = 0.00615-134.87568*x, R2 = 0.9998. Take the dried tea residue activated carbon in Example 4, and then pipette 25mL of 0.05mg / mL ciprofloxacin solution and add it, and perform 1-3h oscillation adsorption on a constant temperature shaking bed at a speed of 100-200rmp / min and a temperature of 20-30°C. After the adsorption experiment was completed, the supernatant was removed using a 5mL syringe and filtered through a 0.45 micron aqueous disposable syringe filter. 0.01mol / L hydrochloric acid was used as a reference solution, and the absorbance was detected by a UV-visible spectrophotometer. The absorption wavelength of ciprofloxacin was 277nm, and the solution concentration was calculated according to the standard curve. Each group of absorbance was measured three times, and the average was taken. The solution concentration was brought into the adsorption rate and adsorption amount formula to calculate the adsorption rate and adsorption amount, and finally the adsorption rate of the tea residue activated carbon in Example 4 was 98.44%.

[0041] The following data are obtained according to the above embodiments and are plotted in Table 1.

[0042] Table 1 Data results of different embodiments of finished products of tea residue activated carbon with high efficiency in adsorbing ciprofloxacin

[0043]

[0044] It can be concluded from the above test data that the tea residue activated carbon prepared by the method of the present invention has a good adsorption effect on ciprofloxacin in water. Compared with the adsorption efficiency of the adsorbent prepared by the traditional method, the tea residue activated carbon prepared by the method adopts the chemical method and the physical method to make the adsorption rate of the prepared tea residue activated carbon reach 98.68%, and the overall process requirements are not high, the process flow is simple, the production cycle is short, and the specific surface area of ​​the prepared tea residue activated carbon is greatly improved. Compared with the traditional activated carbon used for adsorbing ciprofloxacin, it has more obvious advantages and better market prospects.

[0045] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing tea residue activated carbon for efficient adsorption of ciprofloxacin, characterized in that: The process includes the following steps: S1, mixed carbonization process: weigh tea residue powder and 10%-25% sodium chloride in a mass ratio of 1: (1-5), and then place it in a hydrothermal kettle for hydrothermal carbonization, the hydrothermal carbonization temperature is controlled at 150°C-250°C, and the hydrothermal carbonization time is controlled at 3-5h; S2, centrifugal drying process: take out the hydrothermal carbonization product and place it in a centrifuge for 2-3 minutes, and the centrifugal speed is controlled at 500-1000rpm, then take out the solid matter and place it in an electric oven, and dry it in an oven at 90-105℃ for 10-15h; S3, activation process: after the solid material of S2 is dried, it is placed in an atmosphere rotary kiln, the temperature is set and carbon dioxide is introduced as an activation gas for activation, and the activation time is controlled to be 1-4 hours; S4, rinsing and drying process: the product activated in S3 is cooled to room temperature and then taken out, rinsed to neutrality, and then dried in an oven for 10-12 hours, and stored for later use to obtain the product tea residue activated carbon.

2. The method for preparing a tea residue activated carbon with high efficiency in adsorbing ciprofloxacin according to claim 1, characterized in that: In the step S3, the activation temperature in the atmosphere rotary kiln is controlled at 800-900°C, and the heating rate is controlled at 10-15°C / min.

3. The method for preparing a tea residue activated carbon with high efficiency in adsorbing ciprofloxacin according to claim 2, characterized in that: In the step S3, the activation temperature in the atmosphere rotary furnace is controlled to be 900°C, and the heating rate is 10°C / min.

4. The method for preparing a tea residue activated carbon with high efficiency in adsorbing ciprofloxacin according to claim 3, characterized in that: In the step S3, the activation time is 1-1.5 h.

5. The method for preparing a tea residue activated carbon with high efficiency in adsorbing ciprofloxacin according to claim 4, characterized in that: In the step S1, the mass fraction of the selected sodium chloride is in the range of 10-25%.

6. The method for preparing a tea residue activated carbon with high efficiency in adsorbing ciprofloxacin according to claim 5, characterized in that: The mass fraction of sodium chloride in step S1 is 20%. In step S1, tea residue powder is mixed with 20% sodium chloride in a mass ratio of 1:3, and then placed in a hydrothermal kettle for hydrothermal carbonization. The hydrothermal carbonization temperature is controlled at 200°C-230°C, and the hydrothermal carbonization time is controlled at 3-4h.

7. A tea residue activated carbon, characterized in that: The tea residue activated carbon is prepared by any one of the preparation methods of claims 1-6.

8. The tea residue activated carbon according to claim 7, characterized in that: The specific surface area of ​​the tea residue activated carbon obtained is 1700-2100m 2 / g, and the iodine value is within 1500-1800mg / g.

9. The tea residue activated carbon according to claim 8, characterized in that: The specific surface area of ​​the tea residue activated carbon obtained is 1900-2100m 2 / g, and the iodine value is within 1700-1800mg / g.

10. An application of tea residue activated carbon according to claim 8, characterized in that: The tea residue activated carbon is used as an adsorbent to adsorb, degrade and remove ciprofloxacin in a water body containing the ciprofloxacin antibiotic.

Citation Information

Cited By

  • Ciprofloxacin hydrochloride dimer impurity and control and removal method thereof

    CN122277471A